A Simple Microplate Assay for Reactive Oxygen Species Generation and Rapid Cellular Protein Normalization - Ng, Neville; Ooi, Lezanne (Bio-protocol, 2021)
2',7'-dichlorofluorescein (DCF) and derivatives are commonly used as fluorescent indicators of a broad spectrum of reactive oxygen species (ROS) generation in cell-based assays. However, there are numerous challenges inherent to the utilization of DCF probes for intracellular microscopic analysis, including photostability and probe efflux. Plate spectroscopy is comparatively simple and scalable compared to microscopy or flow cytometry-based acquisition, however is often subject to artefacts, including those introduced by thermal gradients and normalization methods. In this protocol we demonstrate a simple and sensitive plate spectrometry-based protocol utilizing the probes H DCFDA and sulforhodamine B. The rapid sulforhodamine B assay (SRB) for cellular protein allows for a stable endpoint measurement of total cell population while also preserving morphology, can be combined or run in parallel with any other assay for normalization of readout to cell mass, and complemented by microscopic scoring of cell number and nuclear count. The oxidative stress and normalisation methods may enhance fields of research investigating cell differentiation, stress, or toxicity.. .